Characteristics of Genetic Susceptibility in Lung Cancer Patients in North Sumatra Population, Indonesia - Putri Aulia Anwar; Noni Novisari Soeroso; Setia Putra Tarigan; Putri Chairani Eyanoer (Indonesian Health Journal, 2026)
Lung cancer remains a major global health problem and the leading cause of cancer-related mortality worldwide. Although smoking and environmental exposure are the dominant risk factors, genetic susceptibility and family history may also contribute to lung cancer development, particularly among individuals with inherited cancer predisposition. This study aimed to describe the characteristics of genetic susceptibility among lung cancer patients in the North Sumatra population, Indonesia, with emphasis on family history of lung cancer and other cancers. A descriptive observational design was employed, conducted from August to November 2024 at Adam Malik Hospital, Universitas Sumatera Utara Hospital, and Santa Elisabeth Hospital. A total of 240 patients with histopathologically confirmed small-cell lung cancer and non-small-cell lung cancer were included through consecutive sampling. Data were collected from medical records, including sociodemographic characteristics, clinical information, and family cancer history, and were analyzed descriptively using IBM SPSS version 26. The results showed that patients had a mean age of 59.12 ± 13.22 years, were predominantly male, and were mostly of Batak ethnicity. Regarding familial susceptibility, 5.4% had a family history of lung cancer, 34.2% had a family history of other cancers, and 60.4% had no family history of cancer. These findings indicate that family history should be considered in lung cancer risk assessment. Integrating familial cancer evaluation into routine clinical practice may support early screening, prevention, and personalized intervention strategies.